The marine Gram-negative bacterium Novosphingobium sp. PP1Y as a potential source of novel metabolites with antioxidant activity - Petruk, Ganna; Roxo, Mariana; Wink, Michael (Biotechnology letters, 2019)
ObjectiveThe antioxidant activity and protective effect of a methanolic extract obtained from the marine Gram-negative bacterium Novosphingobium sp. PP1Y, isolated from the surface water of a polluted area in the harbour of Pozzuoli (Naples, Italy), was evaluated.ResultsThe extract was tested in vitro on epithelial colorectal adenocarcinoma cells and in vivo on Caenorhabditis elegans. It showed strong protective activity against oxidative stress, in both experimental systems, by preventing ROS accumulation. In the case of the cells, pre-treatment with methanolic extract was also able to maintain unaltered intracellular GSH levels and phosphorylation levels of mitogen-activated protein kinases p38. Instead, in the case of the worms, the extract was able to modulate the expression levels of stress response genes, by activating the transcription factor skn-1.ConclusionsFrom a biotechnological and economical point of view, antioxidants from microorganisms are convenient as they provide a valid alternative to chemical synthesis and respond to the ever-growing market demand for natural antioxidants.
Published online: 12 December 2018
Im Titel ist "Novosphingobium" kursiv geschrieben
Gesehen am 03.04.2019